1994
DOI: 10.1111/j.1365-2702.1994.tb00383.x
|View full text |Cite
|
Sign up to set email alerts
|

Occupational stress amongst care staff working in nursing homes: an empirical investigation

Abstract: A questionnaire survey of care staff in nursing homes examined staff stress. Staff completed questionnaires covering Type A behaviour, job satisfaction, psychological well-being, relaxation behaviour, coping skills and demographic details. A specific measure of nursing home stress was developed following a pilot study. From a total sample of 375, 112 (30%) responses were obtained. On the stress questionnaire the major stressors were found to be 'unsatisfactory wages', 'shortage of essential resources', 'not en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 17 publications
1
25
1
3
Order By: Relevance
“…However, it is surprising that the SEQ that was initially designed to assess the stress of carers dealing with dementia (Benjamin and Spector, 1990) seems to be sensitive to the distress of carers in general hospitals where there should be fewer demented patients. Several studies using the SEQ and other similar instruments have shown that facility-related events are more frequently reported by caregivers in nursing homes, particularly organisational (Baillon et al, 1996) and management (Dunn et al, 1994) factors such as low involvement in decision making (Jenkins and Allen, 1998). The present results show a higher frequency of facility-related factors in both types of care-setting though patient-related events (particularly 'aggressiveness', 'lack of confidence towards care-staff' and 'excessive demands') are still fairly frequent in acute geriatric wards.…”
Section: Discussionmentioning
confidence: 98%
“…However, it is surprising that the SEQ that was initially designed to assess the stress of carers dealing with dementia (Benjamin and Spector, 1990) seems to be sensitive to the distress of carers in general hospitals where there should be fewer demented patients. Several studies using the SEQ and other similar instruments have shown that facility-related events are more frequently reported by caregivers in nursing homes, particularly organisational (Baillon et al, 1996) and management (Dunn et al, 1994) factors such as low involvement in decision making (Jenkins and Allen, 1998). The present results show a higher frequency of facility-related factors in both types of care-setting though patient-related events (particularly 'aggressiveness', 'lack of confidence towards care-staff' and 'excessive demands') are still fairly frequent in acute geriatric wards.…”
Section: Discussionmentioning
confidence: 98%
“…18,48 Studies in continuing care settings for older people have come to similar conclusions. 9,11,16,26,28 Few studies, with the exception of Chappell and Novak, 47 have focused on the influence of external factors, such as family support and home life, on work satisfaction, work stress, quality of care and resident/patient well-being in continuing-care settings for older people. This is an important omission, given that women, many of whom take responsibility for caring for a child or an elderly relative, dominate the nursing workforce.…”
Section: Training and Educationmentioning
confidence: 98%
“…11,18,21,22 Other studies have focused on factors closely related to management style and organizational climate. [23][24][25][26][27][28][29][30] Typical of these studies is Schaefer and Moos' 29 investigation of the effect of work stressors and work climate on job morale and functioning of staff in continuing-care settings for older people. They found that both specific work stressors and overall work climate have a significant impact on job morale and functioning.…”
Section: Contextual Factorsmentioning
confidence: 99%
“…This identifies a necessary foundation upon which a more robust system of enhanced staff well-being can exist. Supportive working relationships correlate positively with the well-being of British mental health workers (Wood et al, 2011), while a lack of such relationships is a major predictor of stress (Dunn et al, 1994). Likewise, interpersonal relationships best predicted physical and mental health among hospital nurses in Italy (Pino and Rossini, 2012).…”
Section: Discussionmentioning
confidence: 97%